STUDI KEANEKARAGAMAN JENIS KANTONG SEMAR (Nepenthes spp) DI KAWASAN KONSERVASI RUMAH PELANGI DUSUN GUNUNG BENUAH KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Gultom, Revain Junata; rizal, Fah; Idham, Muhammad (JURNAL HUTAN LESTARI, 2015)
The purpose of this study was to determine the diversity and level of dominance of Kantong Semar in conservation area of Rumah Pelangi. The research used systematic sampling methods in swamp forest area and dry forest area. The sampling line was 200 meter, distance between sampling line was 50 meter and the amount of sampling line was 4 in each vegetation area. Result of research showed that four Kantorng Semar was found i.e. Nepenthes ampullaria Jack, Nepenthes rafflesiana Jack, Nepenthes bicalcarata Hook. f., Nepenthes mirabilis (Lour) Druce. Species in swamp forest area were Nepenthes ampullaria Jack with INP = 80,788%, Nepenthes rafflesiana Jack with INP = 71,92% and Nepenthes bicalcarata Hook.f with INP = 47,29%. Species in dry forest was Nepenthes mirabilis (Lour) Druce with INP = 200%. The dominance species was Nepenthes mirabilis (Lour) Druce with highest diversity (C = 1), meanwhile the lowest dominance species was Nepenthes bicalcarata Hook.f. (C = 0,055). The index of diversity were as follow Nepenthes rafflesiana Jack ( = 0,159), Nepenthes ampullaria Jack ( = 0,158), Nepenthes bicalcarata Hook.f. ( = 0,147) and Nepenthes mirabilis (Lour) Druce ( = 0) respectively. The value of highest diversity was Nepenthes rafflesiana Jack with species diversity 0, 264 and the lowest was Nepenthes mirabilis (Lour) Druce. Keyword : Nepenthes ampullaria Jack, Nepenthes rafflesiana Jack, Nepenthes bicalcarata Hook. f., Nepenthes mirabilis (Lour) Druc, index diversity, dominancy